Recent advances in Merkel cell carcinoma - Robinson, Caitlin G. (F1000Res, 2019)
Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine skin cancer that has been historically associated with limited treatment options and poor prognosis. In the past 10 years, research in MCC has progressed significantly, demonstrating improved outcomes when treating with immunotherapy, particularly PD-1/PD-L1 inhibitors, when compared with conventional chemotherapy. There is also increasing evidence of the abscopal effect, a phenomenon describing the regression of untreated, distant MCC tumors following local radiation therapy. Additionally, antibodies to Merkel cell polyomavirus oncoproteins have been found to correlate with disease burden in a subset of patients, providing a useful tool for surveillance after treatment. Guidelines for the management of MCC will likely continue to change as research on surveillance and treatment of MCC continues.